Polypharmacological potential of natural compounds against prostate cancer explored using molecular docking and molecular dynamics simulations. (10th May 2020) - Antony, Priya; Baby, Bincy; Homedi, Zahrah Al; Halabi, Walaa Al; Ali, Amanat; Vijayan, Ranjit
Prostate cancer is one of the most frequently diagnosed forms of cancer. Over expression of several non-receptor tyrosine kinases (NRTKs) have been observed in prostate cancer. Three NRTKs - Bruton's tyrosine kinase (BTK), focal adhesion kinase (FAK) and Src kinase - were considered in this study. Virtual screening of the InterBioScreen natural compounds library identified four compounds - STOCK1N 32236, STOCK1N 30449, STOCK1N 24193 and STOCK1N 23077 - that are structurally similar and possessed polypharmacological properties by interacting with all the three NRTKs in a similar manner by orienting one naphthalene group towards the hinge region and another towards the activation loop. Binding score and interactions of these natural compounds were better than currently available kinase inhibitors. 100 ns molecular dynamics simulation showed that these molecules bound stably in the active site. The screened natural molecules could be a framework for developing novel kinase inhibitors for the treatment of prostate cancer.